Asian transnational organized crime - Finckenauer, James O. (Nova Science Publishers, 2007)
Leading organized crime problems -- Asian authorities' perspective -- American authorities' viewpoint -- Scope and patterns of organized crime -- Specialization -- Structure or opportunity? -- The flow -- Threat, impact and harm to the United States